Whose small bowel biopsy is this? AIDS from molecular biology : Use of molecular techniques for mismatched specimen identification - Quijano, Graciela (2002)
We report here an episode of mismatched small bowel biopsies that happened in our laboratory, and the way in which it was solved through PCR technique investigation. The procedure allowed a rapid and accurate identification of the samples, avoiding any harm to the patients involved.